Fenomena Cashless Society Pada Generasi Milenial dalam Menghadapi COVID-19 - dini haryati (Jurnal Inovasi Bisnis dan Kewirausahaan, 2021)
The millennial generation is a generation that was born between the 1980s and the present. This generation is very familiar with the world of digital-based technology. The use of gadgets is part of their lifestyle. The number of social media users among millennials is quite large, reaching 93%. Moreover, at this time, the risk of being infected with the corona virus in financial transactions is a direct concern of the public in every purchasing activity. So that people prefer to use contactless financial transactions by making payments through digital wallet applications. This study aims to determine the phenomenon of cashless society in the millennial generation in dealing with Covid-19. In this study, the researcher chose to use a qualitative research type. Data collection techniques were carried out by interview, non-participant observation method on 15 key informants of students of the Batanghari Nusantara Islamic Institute. The results showed that most people, especially millennials, used the OVO, Shopee, Link Aja, Dana and other applications during the Covid-19 pandemic. By using a payment instrument like this it makes it easier for public services to reduce the risk of being infected with the corona virus.